2017
DOI: 10.3324/haematol.2017.181941
|View full text |Cite
|
Sign up to set email alerts
|

Macrocytosis and dysplastic anemia is associated with the cyclin-dependent kinase 4/6 inhibitor palbociclib in metastatic breast cancer

Abstract: dysplastic anemia is associated with the Cyclin-Dependent Kinase 4/6 inhibitor palbociclib in metastatic breast cancer. Haematologica. 2017; 102:xxx doi:10.3324/haematol.2017.181941 Publisher's Disclaimer. Hematopoiesis is a dynamic process that relies on active proliferation and differentiation of stem cells into erythrocytes, myelocytes, and platelets; processes that rely on coordinated progression through various phases of the cell-cycle. Neutropenia is a well-recognized adverse effect of palbociclib, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Macrocytosis (elevation of MCV above upper normal limit) has developed in 31 out of 82 patients (38%) treated with AC-T dose-dense chemotherapy. This was less than expected in comparison to previously published results with chemotherapy in metastatic breast cancer (47-61%), as well as in our investigation of macrocytosis induction in ovarian cancer patients (67%) [12,14,15]. Similar to other reports, MCV elevation was accompanied by only mild drop in hemoglobin levels during treatment, which did not differ significantly between macrocytosis and no macrocytosis group [16].…”
Section: Response Rate Analysiscontrasting
confidence: 79%
“…Macrocytosis (elevation of MCV above upper normal limit) has developed in 31 out of 82 patients (38%) treated with AC-T dose-dense chemotherapy. This was less than expected in comparison to previously published results with chemotherapy in metastatic breast cancer (47-61%), as well as in our investigation of macrocytosis induction in ovarian cancer patients (67%) [12,14,15]. Similar to other reports, MCV elevation was accompanied by only mild drop in hemoglobin levels during treatment, which did not differ significantly between macrocytosis and no macrocytosis group [16].…”
Section: Response Rate Analysiscontrasting
confidence: 79%
“…An additional cohort study showed development of macrocytosis and red cell dysplasia in 34 patients treated with palbociclib, typically after 4 cycles. The dysplastic changes were reversible on discontinuation of palbociclib [16]. Although our patient developed worsening anemia with mildly elevated MCV, dysplastic changes were not seen in the bone marrow aspirate.…”
Section: Discussionmentioning
confidence: 88%
“…MDS, with reversible macrocytic anemia, attributed to palbociclib has been reported recently. Three cases of reversible MDS were observed and reported by Anampa et al [16]. These patients had dysplastic changes in their peripheral blood, and they all had bone marrow aspirates/biopsies which also showed dysplastic changes in erythroid precursors and megakaryocytes with bone marrow cellularity of about 10%.…”
Section: Discussionmentioning
confidence: 93%
“…Patients treated with CDK4/6 inhibitors frequently develop anemia. 28 , 38 In order to understand the contribution of CDK4 or CDK6 in this process, we studied erythroid development in Cdk4 D/D and Cdk6 D/D mice and their littermate controls. Cdk4 D/D and Cdk6 D/D mice displayed significantly reduced numbers of RBC in peripheral blood.…”
Section: Resultsmentioning
confidence: 99%
“…CDK4/6 inhibitor-associated side effects manifest primarily in the hematopoietic system and include anemia, neutropenia and lymphopenia. 28 , 29 , 38 As attempts are ongoing to develop CDK inhibitors that will more specifically target individual CDK it is important to attribute side effects to either CDK4 or CDK6. We analyzed novel mouse models harboring floxed Cdk4 or Cdk6 alleles and deleted CDK4 or CDK6 in adult hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%